Determination of dissolved inorganic carbon (DIC) and dissolved organic carbon (DOC) in freshwaters by sequential injection spectrophotometry with on-line UV photo-oxidation - Tue-Ngeun O. (2014)
An automated sequential injection (SI) method for the determination of dissolved inorganic carbon (DIC) and dissolved organic carbon (DOC) in freshwaters is presented. For DIC measurement on-line sample acidification (sulphuric acid, pH < 2), converted DIC to CO2 which subsequently diffused through a PTFE membrane into a basic, cresol red acceptor stream. The CO2 increased the concentration of the acidic form of the cresol red indicator, with a resultant decrease in absorbance at 570 nm being directly proportional to DIC concentration. DIC + DOC was determined after on-line sample irradiation (15 W low power UV lamp) coupled with acid-peroxydisulfate digestion, with the subsequent detection of CO2 as described above. DOC was determined by subtraction of DIC from (DIC + DOC). Analytical figures of merit were linear ranges of 0.05-5.0 mg C L-1 for both DIC and DIC + DOC, with typical R.S.D.s of less than 7% (0.05 mg C L-1-5.3% for DIC and 6.6% for DIC + DOC; 4.0 mg C L-1-2.6% for DIC and 2.4% for DIC + DOC, n = 3) and an LOD (blank + 3S.D.) of 0.05 mg C L-1. Sample throughput for the automated system was 8 h-1 for DIC and DOC with low reagent consumption (acid/peroxydisulfate 200 μL per DIC + DOC analysis). A range of model carbon compounds and Tamar River (Plymouth, UK) samples were analysed for DIC and DOC and the results showed good agreement with a high temperature catalytic oxidation (HTCO) reference method (t-test, P = 0.05). © 2005 Elsevier B.V. All rights reserved.